Regional Financing: Spanish Autonomous Communities Versus German Laenders - Carmen Lopez Martin; Pedro Pablo Perez Hernandez; Araceli Rios Berjillos (European Regional Science Association (ERSA), 2006)
Spanish state descentralization is very similar to the most important federal countries. In spite of the advances in the regional financing system it hasn't been able to give the needed autonomy and financial sufficiency to fund the transferred competencies in the Spanish Autonomies. From 1987 to nowdays four different models of financiation have been implemented. The last one, approved in 2001 and though it seemed to be succesfull, it is going to be remodelled shortly . There are objective reasons to justify the system modification: evolution of the public expenses, inmigration, in general terms, society evolution. However, it is a political reason what has brought this topic on. Last proposal comes from the Catalonian Government. Some parts of the proposal take as model the German länder financial system, specially the basket tax and the interregional solidarity system. The aim of this research is to compare socioeconomic features in regions belonging to Germany and Spain as well as their financial system in order to know what can be useful to Autonomic Spanish financial system taken from the German one. The methodology used is the following one: a) First of all, we have studied the main socioeconomic features of Spanish regions and of German länders. In this part of the work, we have been able to get similarities between regions in both countries. Similarities that can justify directly or indirectly some aspects of the financing. b) Secondly, it has been made a description of the financial system applied in German länders and in the Spanish Autonomies. It has been specially compared the extent of autonomy and solidarity in each system. c) Thirdly, it has been studied the reform proposed by the Catalonian Government identifying its relation to the German regional financial system. d) And finally, it has been made a valoration about the Catalonian Government proposals and some other conclusions have been drawn over the possibility to implement German system to Spanish regions.
Keywords: 330